Analisis Dalam Pengurusan Surat Izin Usaha Di Indonesia Dan Singapore - Dakhi, Grace Irene; Dompak, Timbul; Khairina, Etika (LPPM Universitas Putera Batam, 2024)
The rapid growth in the commercial sector has turned society into an economic driver. Many corporations start by setting up a corporation to carry out their business activities. It is important for business owners to obtain a commercial permit as a business document confirming the legality of the business activity carried out. Local governments have an important role to play in granting business permits, and adaptations to the centralized regional integrated service system (OSS) have been made to improve public service. However, the implementation of OSS still faces some obstacles, including inconsistencies between central and regional governments as well as dualism in regional management. Singapore, on the other hand, offers faster, more efficient, and more conducive business licensing processes for entrepreneurs. Singapore’s government actively supports industry and foreign companies through friendly regulations and a supportive business environment. Previous research has highlighted that although efforts have been made to simplify the process of licensing through OSS in Indonesia, there is still room for improvement in coordination between central and regional governments as well as in the comprehensive implementation of regulations. In the context of research methods, this study uses a qualitative approach to comparative studies between Indonesia and Singapore. The results and interpretation show that significant differences in business licensing processes between the two countries affect the attractiveness of global entrepreneurs. In conclusion, Singapore offers a more conducive business environment and a more efficient licensing process compared to Indonesia. This emphasizes the need for further reforms in the Indonesian license system to increase competitiveness and facilitate investment and economic growth